New results to the inverse optimal control problem for discrete-time linear systems - Iracleods, Dimitris P.; Alexandridis, Antonio T. (Zielona Góra: Uniwersytet Zielonogórski)
The inverse optimal control problem, i.e. the problem of the optimal eigenvalue assignment for multi-input linear discrete-time systems, is considered. New necessary and sufficient conditions are proposed which lead to new simple optimal design methods. In particular, for an n-th order system with m inputs the proposed method assigns n ? m dominant eigenvalues to any preselected positions while the remaining m eigenvalues are accommodated to ensure stability and to satisfy optimal criteria.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka